2003
DOI: 10.1007/s10067-002-0691-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different viscosupplements in knee osteoarthritis - a pilot study

Abstract: A pilot study was designed to investigate the efficacy of two different hyaluronic acid preparations combined to physical therapy in patients with knee osteoarthritis in terms of reduction in pain and disability and muscle strengthening. Thirty-seven patients with symptomatic osteoarthritis of the knees were randomly assigned into three groups. First group received a lower molecular weight hyaluronic acid plus physical therapy, second group received a higher molecular weight hyaluronic acid plus physical thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
19
0
3
Order By: Relevance
“…The implications of molecular weight in viscosupplementation therapy has been extensively discussed in the literature, 36 -39 but to date only in vitro experiments and animal models 15,16,40,41 have clearly supported the contention that higher molecular weight derivatives may lead to enhanced rheologic properties, more effective inflammatory inhibition, and potentially better symptomatic improvement than their lower molecular weight counterparts. One clinical pilot study in the literature demonstrated no difference between hylan and hyaluronan with regard to muscle strengthening and knee scores, 42 and a recent clinical trial showed no difference in functional outcome measures between hylan and sodium hyaluronate in patients with severe knee OA 1 year after 3 injections. 43 In the current investigation, at follow-up visits of approximately 3 months and 6 months, the hylan group was FIGURE 3: VAS pain scores.…”
Section: Discussionmentioning
confidence: 98%
“…The implications of molecular weight in viscosupplementation therapy has been extensively discussed in the literature, 36 -39 but to date only in vitro experiments and animal models 15,16,40,41 have clearly supported the contention that higher molecular weight derivatives may lead to enhanced rheologic properties, more effective inflammatory inhibition, and potentially better symptomatic improvement than their lower molecular weight counterparts. One clinical pilot study in the literature demonstrated no difference between hylan and hyaluronan with regard to muscle strengthening and knee scores, 42 and a recent clinical trial showed no difference in functional outcome measures between hylan and sodium hyaluronate in patients with severe knee OA 1 year after 3 injections. 43 In the current investigation, at follow-up visits of approximately 3 months and 6 months, the hylan group was FIGURE 3: VAS pain scores.…”
Section: Discussionmentioning
confidence: 98%
“…Bayramoglu et al, 66 2003 Hylan G-F 20 = HA for HSS pain score for pain relief at 52 wk Karatosun et al, 63 2005 Hylan G-F 20 = HA for pain relief on HSS pain score at 52 wk Atamaz et al, 64 2006 Hylan G-F 20 = HA using the WOMAC pain scale for pain relief at 1, 3, 6, 9, and 12 mo Juni et al, 65 2007 Hylan G-F 20 = HA using the WOMAC pain scale for pain relief at 3 and 6 mo However, safety concerns about the use of acetaminophen and NSAIDs should be considered. Acetaminophen is prescribed for OA knee pain at a dose up to 4 g/d.…”
Section: Safety Of Viscosupplementationmentioning
confidence: 98%
“…Published data suggest that intra-articular injections of HA in hip OA are effective in the relief of pain (13)(14)(15). Studies comparing a combination of intra-articular HA injections and exercise to exercise alone in patients with knee OA showed promising results (16,17). However, no similar studies have been performed in hip OA.…”
Section: Introductionmentioning
confidence: 92%